Crime and crime prevention in China: A C: a challenge to the development-crime nexus - Friday, Paul C. (Journal of contemporary criminal justice, 1998)
Since China's new open door policy, major economic and social changes have occurred as well as a demonstrated increase in official and victim survey reports on crime. The patterns of crime and characteristics of offenders parallels that of Western societies, but the rate of crime is still very low. A major increase in crime is not necessarily an outcome of development, where cultural and social history and philosophy have established strong prevention roots. The most recent literature on changes occurring in China are reviewed within theoretical perspectives linking development and crime: Durkheimian Modernization, Marxist, and Victimological. Chinese programs and crime-prevention policies are discussed and evaluated based on individual and systemic correlates of crime and the theoretical needs for prevention. Chinese culture and tradition are seen as preventive mechanisms in and of themselves and, therefore, need to be reinforced as China experiences major social change.